To simplify the expression and keep only positive exponents, we can use the rule:
\(a^{-b} = \frac{1}{a^b}\)
Applying this rule to the expression:
\(15^0 \cdot 7^{-2} \div (-4)^{-3}\)
We have:
\(15^0 = 1\) (Any number raised to the power of 0 is equal to 1)
\(\frac{1}{7^2} = \frac{1}{49}\) (Using the rule \(a^{-b} = \frac{1}{a^b}\))
\(\frac{1}{(-4)^{-3}} = \frac{1}{\left(\frac{1}{(-4)^3}\right)} = -64\) (Applying the rule to the negative exponent)
Therefore, the simplified expression is:
\(1 \cdot \frac{1}{49} \div -64 = \frac{1}{49} \div -64 = -\frac{1}{3136}\)
which of the following is an equivalent expression to 15^0∙7^-2/(-4)^-3
only positive exponents that has been generated
1 answer